Degree of projectification in the financial sector in the Czech Republic and its impact on strategic capabilities - Tordo da Silva, Lucas; Hájek, Jiří; Krupa, Miroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Projectification is a relatively recent concept, and researchers have only recently uncovered its implications. This thesis explores projectification in the financial sector of the Czech Republic and its impacts on the innovative and flexibility capacities of firms. This study is inspired by similar research conducted in other sectors and its methodology is partly adapted from the studies on the projectification of Germany, Norway and Iceland. The main goals of this thesis are to quantify the level of projectification of financial firms, to measure its impact on innovation and flexibility and to compare the findings of the estimated model with other studies. A sample of 15 representative firms from the sector was interviewed by phone and online surveys. The collected data was used to apply descriptive statistical analysis to characterise the industry in terms of the usage of projects, its innovativeness and strategic flexibility. The estimated projectification level of the Czech financial sector was 21,61% in 2021. Findings from the estimated linear regression models suggest that projectification has a positive and robust impact on innovation, as well as a positive and weak impact on flexibility. The data showed that the Czech financial industry lags behind its European peers in the level of projectification. The limited sample size prevents inferences to the entire financial sector, but statistical robustness was increased to validate the conclusions taken.
Vedoucí práce: Jiří Hájek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses